Impact of Time Taken on the Surgical Outcome of Extradural Hematoma in Patients with Road Traffic Accidents - Muhammad Mujahid Sharif , Adil Aziz Khan , Rayif Rashid Kanth , Ali Tassadaq Hussain Minhas, Muhammad Mujahid Sharif , Adil Aziz Khan , Rayif Rashid Kanth , Ali Tassadaq Hussain Minhas (Journal of Rawalpindi Medical College, 2017)
Background: To determine the impact of time taken on the surgical outcome of extradural hematoma in patients with road traffic accidents. Methods: Sixty adult patients with history of road traffic accident with extradural hematoma on axial images of CT scan brain were included. All patients were allocated into three groups with 20 patients in each group. Patients in Group I were those in whom time from the occurrence of trauma to the surgical evacuation of hematoma was < 1 hour, 1 to 6 hours in group II and > 6 hours in group III. Results: In group I, majority (90 %) showed favourable outcome. In group II, 70 % showed favourable outcome. In group III, 50 % showed favourable outcome. Significant association was found between outcome and time of surgery (p<0.05). Conclusions: Frequency of favourable outcome after surgical evacuation was significantly higher in patients in whom surgery was performed within one hour after the trauma (P<0.05).